Potential of a novel and thermostable recombinant phage endolysin of Escherichia phage KW1E_UTAR against Shigella spp. - Selvam Dharshini; Mohd Ismail Nor Ismaliza; Ng Michelle Y. T. (E3S Web of Conferences)
Shigella causes millions of cases and hundreds of thousands of deaths annually, mainly affecting children in impoverished countries. Shigellosis outbreaks have been linked to waterborne transmission, and chlorination is commonly used to disinfect water. However, the emergence of chlorine-resistant Shigella spp. is a concern. Therefore, it is imperative to develop an alternative antibacterial agent such as endolysin against the Shigella spp. In this study, the Escherichia phage KW1E_UTAR gene encoding for endolysin was successfully cloned and expressed in Escherichia coli pET-28a. The purified endolysin was characterized, and its antibacterial activity was determined. The purified endolysin remained stable between pH 4 and 9, and at a broad range of temperature (4°C–75°C). The endolysin's storage stability was tested for one week, one month, and three months at different temperatures (4°C, −20°C, and −80°C). Despite over 50% drop in the lytic activity, the purified endolysin outperformed the commercial lysozyme. Besides, all four Shigella spp. tested were susceptible to the purified endolysin, with Shigella flexneri being the most prominent. Subsequently, the purified endolysin’s effectiveness in removing S. flexneri from spiked water samples was evaluated. After an hour of treatment, the number of viable bacteria in the water samples was reduced by 99.9%. Therefore, endolysin could be effective at eradicating Shigella spp. in various water sources.